If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 59 = k + -4 Reorder the terms: 59 = -4 + k Solving 59 = -4 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 59 + -1k = -4 + k + -1k Combine like terms: k + -1k = 0 59 + -1k = -4 + 0 59 + -1k = -4 Add '-59' to each side of the equation. 59 + -59 + -1k = -4 + -59 Combine like terms: 59 + -59 = 0 0 + -1k = -4 + -59 -1k = -4 + -59 Combine like terms: -4 + -59 = -63 -1k = -63 Divide each side by '-1'. k = 63 Simplifying k = 63
| 5(a^2)+6a-8=0 | | 4=62-e | | X+11v+4x-v= | | 79-x=1 | | 60-x=41 | | 11+5z=6 | | 4=87-y | | (4y^2)+3y-1=0 | | (5x-9)(9x+8)=0 | | 90-m=1 | | 96-p=63 | | (9k^2)-9k+2=0 | | 26t+5a-4t-2= | | r-28=33 | | 84-v=29 | | (7z^2)-10z+3=0 | | 71-x=22 | | 8x-5=2x+11 | | 47=c-31 | | X^2+10x-11x=0 | | w/-6=-9 | | a-16=12 | | 45=79-h | | 7c+3=17 | | 45=54-d | | 47=54-d | | (8Z^2)+14z+5=0 | | 62=81-r | | 12i+7r-14i= | | 12i+7r-14y= | | 3t+1=7t | | 6a^2-13a+15=6a |